The Role of Network Infrastructure in Supporting Business Connectivity in the Lombok Region - Akbar, Rizky Falian (Raudhah Publisher, 2024)
This study explores the role of network infrastructure in enhancing business connectivity within the Lombok region, utilizing qualitative methods, literature review, and library research. As digital transformation progresses, reliable and efficient network infrastructure has become crucial for business operations. This research identifies key challenges and opportunities associated with network infrastructure in Lombok, including issues related to accessibility, bandwidth capacity, and network stability. By reviewing various scholarly sources and case studies, the study analyzes how network infrastructure contributes to improving communication, collaboration, and productivity among businesses in the region. Furthermore, it highlights the significance of government and private sector investment in developing robust infrastructure to foster regional economic growth. The findings suggest that while certain areas in Lombok still face limitations in network connectivity, ongoing efforts to upgrade infrastructure have started to bridge the digital divide, creating a more competitive business environment. The study concludes that enhancing network infrastructure is vital for supporting business operations, especially as more businesses transition to digital platforms. This research offers insights into potential strategies to address existing network challenges and emphasizes the need for continuous investment and innovation to ensure sustained economic development in Lombok through improved connectivity.